FEMALE AVENGER: VIOLENCE, ABSURDITY, AND BLACK HUMOUR IN ROALD DAHL’S SHORT STORIES - 528, Ms. Jashandeep Kaur, Ms.Amolak (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Dahl's short stories criticise women's societal roles in the mid-nineteenth century. Dhal presents women who defy standard gender boundaries and move from domestic to criminal domains in startlingly horrible ways in one narrative after another. His female characters depict the "feminine mystique" — the inconsistencies and tensions those post-year years witnessed over gender roles in society. What appears to be a common and recurring concept that runs through all three elements of this triangle is revenge? Dahl introduces avenger models in one storey after another. His female avenger is a picture of a woman who is obsessed with getting revenge and succeeds no matter what she does. In Dahl's short stories, the female avenger is a character who is mean and clever when she wants to get revenge on the male protagonist, even though her actions are sometimes surprising and unexpected. A lot of people read Dahl's stories, and this one will look at three that show female avengers at work. When we talk about some Dahl short stories, we'll pay attention to how the female avenger fits into Dahl's mix of black humour, absurdity, and violence.